Multicenter study to assess presenteeism in systemic lupus erythematosus and its relationship with clinical and sociodemographic features. (January 2018) - Cosatti, M A; Muñoz, S; Alba, P; Helling, C A; Roverano, S; Sarano, J; Malm-Green, S; Danielsen, M; Medina Bornachera, D; Alvarez, A; Eimon, A; Pendón, G; et al.
Objective: The aim of this study was to measure presenteeism (productivity impairment while the patient is at work) and the related risk factors in patients with systemic lupus erythematosus (SLE) from Argentina. Methods: A total of 130 consecutive (1997 American College of Rheumatology (ACR) criteria) working patients with SLE were assessed using a standardized data collection form. Sociodemographic, disease and work-related variables were collected. The Work Productivity and Activity Impairment (WPAI) questionnaire was performed. Results: Overall, 130 patients were included in the analysis; 91% were women, and the mean age was 39 years (range 19–77). A total of 43% were White, 43% Mestizo and 13% Amerindian. Overall, 38% were single and 38% were married. A total of 75% had more than 12 years of formal education. The median disease duration was 7 years (interquartile range 25–75 (IQR) 4–13). Median Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) score was 0 (IQR 0–2), and median Systemic Lupus International Collaborating Clinics/ACR Damage Index (SLICC-SDI) score was 0 (IQR 0–1). Lupus quality of life (LupusQoL) domains scores were: physical health 87 (IQR 70–96), emotional health 78 (IQR 54–91), burden to others 75 (IQR 50–92), intimate relationships 87 (IQR 50–100), and body image 85 (IQR 70–100). Absenteeism was 8%, presenteeism was 19%, and overall work impairment (absenteeism + presenteeism) was 26%. In the multiple regression analysis, considering presenteeism as dependent variable, (adjusting by age, disease duration, >12 years of education, Non-white race, Visual Analogue Scale (VAS) pain, VAS fatigue, SLICC-SDI, LupusQoL, physical and emotional domains), we found that SLICC-SDI (odds ratio (OR) 1.68, confidence interval (CI) 1–2.7) and Non-white race (OR 3.27, CI 1.04–10) were related to presenteeism and >12 years of education (OR 0.30, CI 0.09–0.98) and higher scores of LupusQoL emotional health domain (OR 0.95, CI 0.92–0.98) were protective. Conclusions: organ damage and Non-white race were significantly associated with presenteeism while >12 years of education and higher scores of LupusQoL emotional health domain were protective.